Simultaneous nutrient removal and lipid production from pretreated piggery wastewater by Chlorella vulgaris YSW-04 - Ji, Min-Kyu; Kim, Hyun-Chul; Sapireddy, Veer Raghavulu; Yun, Hyun-Shik; Abou-Shanab, Reda A. I.; Choi, Jaeyoung; Lee, Wontae; Timmes, Thomas C.; Inamuddin; Jeon, Byong-Hun (SPRINGER, 2013)
The feasibility of using a microalga Chlorella vulgaris YSW-04 was investigated for removal of nutrients from piggery wastewater effluent. The consequent lipid production by the microalga was also identified and quantitatively determined. The wastewater effluent was diluted to different concentrations ranging from 20 to 80 % of the original using either synthetic media or distilled water. The dilution effect on both lipid production and nutrient removal was evaluated, and growth rate of C. vulgaris was also monitored. Dilution of the wastewater effluent improved microalgal growth, lipid productivity, and nutrient removal. The growth rate of C. vulgaris was increased with decreased concentration of piggery wastewater in the culture media regardless of the diluent type. Lipid production was relatively higher when using synthetic media than using distilled water for dilution of wastewater. The composition of fatty acids accumulated in microalgal biomass was dependent upon both dilution ratio and diluent type. The microalga grown on a 20 % concentration of wastewater effluent diluted with distilled water was more promising for generating high-efficient biodiesel compared to the other culture conditions. The highest removal of inorganic nutrients was also achieved at the same dilution condition. Our results revealed the optimal pretreatment condition for the biodegradation of piggery wastewater with microalgae for subsequent production of high-efficient biodiesel.